Near-Infrared Spectroscopy: Recent Advances in Infant Speech Perception and Language Acquisition Research - Judit Gervain (Frontiers Research Topics, 2015)
Near-Infrared Spectroscopy (NIRS) is a novel and increasingly popular optical imaging technique that has revolutionarized brain research in the youngest developmental populations. After nearly a decade of technological development, NIRS has become a reliable, easy-to-use and efficient tool to explore the linguistic and cognitive abilities of neonates and young infants, opening new vistas for the investigation of language acquisition and cognitive development. This Research Topic covers the latest advances in these areas brought about by NIRS imaging. The main focus is to highlight innovative and foundational studies that go beyond methodological issues and advance our theoretical understanding of infant and child development. Contributions from the pioneers of this method are selected, illustrating how NIRS has allowed developmental researchers to ask theoretically relevant questions that more traditional methods couldn't address. These works further our understanding of language and cognitive development and bring us closer to bridging the gap between brain, mind and behavior at the very beginning of life.